Publisher Correction: Using micro-computed tomography to reveal the anatomy of adult Diaphorina citri Kuwayama (Insecta: Hemiptera, Liviidae) and how it pierces and feeds within a citrus leaf - Javier Alba‑Tercedor (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.